2020
DOI: 10.1002/xrs.3212
|View full text |Cite
|
Sign up to set email alerts
|

Mudirac: A Dirac equation solver for elemental analysis with muonic X‐rays

Abstract: We present a new open‐source software for the integration of the radial Dirac equation developed specifically with muonic atoms in mind. The software, called mudirac, is written in C++ and can be used to predict frequencies and probabilities of the transitions between levels of the muonic atom. In this way, it provides an invaluable tool in helping with the interpretation of muonic X‐ray spectra for elemental analysis. We introduce the details of the algorithms used by the software, show the interpretation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…used as an alternative to predict frequencies and probabilities of the transitions between levels of the muonic atom [21].…”
Section: Comparison With the Experimental Resultsmentioning
confidence: 99%
“…used as an alternative to predict frequencies and probabilities of the transitions between levels of the muonic atom [21].…”
Section: Comparison With the Experimental Resultsmentioning
confidence: 99%
“…Indeed, it has been found that, especially for high Z atoms and high-energy transitions, there is a large deviation from simulated and measured values, as explained in the next paragraphs. Here, we propose a new approach that involves the creation of a new database of transition energies produced by an open-source Dirac equation Solver called MuDirac, developed by the UKRI scientific computing department and the ISIS Muon group [27].…”
Section: Introductionmentioning
confidence: 99%